Structural studies of B-type Aurora kinase inhibitors using computational methods - Neaz Mm; Muddassar M; Pasha Fa; Joo Cho Seung (Acta Pharmacologica Sinica, 2016)
Aim: To characterize the structural features of quinazoline-based Aurora B inhibitors that influence its inhibitor activity. Methods: Two geometrical methods, Method 1 and Method 2, were used to develop the 3D-QSAR models. The most active ligand was used as the template for the alignment of all the ligands in Method 1, and a conformer of the cocrystal ligand was used as the template for the alignment of all the ligands in Method 2. Results: The models suggest that highly active ligands can be designed by varying the R1 substituent at position 7 of the quinazoline ring with positively charged, bulky, hydrophobic groups, while bulky and hydrophobic groups around the thiazole ring are desirable for higher activity. Conclusion: This study emphasizes that the bioactive conformer is rather different from the minima. The steric, electrostatic, and hydrophobic field effects contribute to its inhibitory activity.